Medieval Arabic Historiography - Hirschler, Konrad (SOAS/Routledge Studies on the Middle East, 2006)
Medieval Arabic Historiography is concerned with social contexts and narrative structures of pre-modern Islamic historiography written in Arabic in seventh and thirteenth-century Syria and Eygpt. Taking up recent theoretical reflections on historical writing in the European Middle Ages, this extraordinary study combines approaches drawn from social sciences and literary studies, with a particular focus on two well-known texts: Abu Shama's The Book of the Two Gardens, and Ibn Wasil's The Dissipater of Anxieties. These texts describe events during the life of the sultans Nur-al-Din and Salah al-Din, who are primarily known in modern times as the champions of the anti-Crusade movement. Hirschler shows that these two authors were active interpreters of their society and has considerable room for manoeuvre in both their social environment and the shaping of their texts. Through the use of a fresh and original theoretical approach to pre-modern Arabic historiography, Hirschler presents a new understanding of these texts which have before been relatively neglected, thus providing a significant contribution to the burgeoning field of historiographical studies.